Assessing the biomechanical characteristics of defensive movements in elite boxers of different competitive levels - Wang, X.; Korobeynikov, G. (BMC Sports Science, Medicine and Rehabilitation, 2026)
Background The purpose of this study was to identify biomechanical patterns that determine the efficiency and stability of performing defensive movements in highly qualified boxers, and to establish relationships between the level of athletic training and the nature of motor strategies.